Modelling and simulation of different electrode size for electrostatic sensors - Heydarianasl, Mozhde (2015)
Electrostatic sensor has been widely used in process industry in addition this sensing approach has attracted significant attention of flow measurement community because of its advantages including robustness and low costs. This paper focuses on the theoretical analysis of several electrostatic electrodes, including ring, quarter-ring, pin, and rectangular; after that, they are mathematically modelled and simulated by Mathcad software. The geometric measurements of electrodes are considered as important parameters, which affect the results of simulation. However, spatial sensitivity and statistical error are the sensing characteristics of electrodes, which play major roles in modelling these electrodes. The thickness of an electrode, as a parameter influencing spatial sensitivity, is investigated in this study. Increasing the thickness of electrode leads to increase both spatial sensitivity and statistical error while maximum spatial sensitivity and minimum statistical error are desirable parameters. Therefore, the best thickness value of an electrode must be determined to achieve the required uniform spatial sensitivity. Good verification between experimental tests and the mathematical model suggests a reasonable model of electrostatic sensor electrodes.